Removal of Congo red and methylene blue using H2O2 modified activated carbon by microwave regeneration: isotherm and kinetic studies. (23rd August 2019) - Zhang, Qi; Cheng, Song; Xia, Hongying; Zhang, Libo; Zhou, Junwen; Jiang, Xin; Hu, Wenhai; Chen, Quan
Abstract: Microwave-assisted heating technology was used for treating paracetamol decolorizing spent activated carbon (SAC). The regenerated activated carbon (RAC) was modified using hydrogen peroxide (H2 O2 ) to obtain modified activated carbon (MRAC), which was used for removing Congo red (CR) and methylene blue (MB) in aqueous solution, achieving the goal of utilizing hazardous waste resources. The RAC BET surface area was 1254.46 m 2 g −1, and the results showed that microwave treatment could effectively regenerate the spent carbon. To increase the adsorption capacity of activated carbon, the surface was modified with H2 O2 to increase oxygen-containing functional groups. The adsorption behavior of CR and MB on MRAC was studied, and equilibrium data were simulated by using the Langmuir, Freundlich, Redlich–Peterson, and Temkin isotherm models. The isotherm experimental data were best fitted by the Redlich–Peterson model, and the maximum sorption capacities obtained were 254 and 318 mg g −1 for CR and MB on MRAC (7% H2 O2 ), respectively. The adsorption kinetics were best described by the pseudo-second-order model, and the Weber–Morris model showed that the adsorption process includes three stages: boundary layer diffusion and two intra-particle diffusion stages. The kinetic and isotherm experimental evidence showed the high efficiency of MRAC (7% H2 O2 ) adsorption for CR and MB and its potential for organic pollutant removal.